Efektivitas Konseling Seksual untuk Keharmonisan Keluarga Pasien Penyakit Ginjal Kronis Usia Reproduktif Yang Menjalani Hemodialisis di Rumah Sakit Haji Jakarta - Siti Aminah; Yani Sofiani; Wati Jumaiyah (FORIKES, 2021)
Sexual dysfunction in patients with chronic kidney disease does not only occur in male patients, but also occurs in female patients. Patients who experience sexual dysfunction due to chronic kidney disease undergoing hemodialysis will feel inferior, frustrated, irritable, irritable, stressed, depressed, and even avoid having sex with their partners. These problems can affect the harmony in the family. One of the efforts to overcome sexual dysfunction in hemodialysis patients needs the role of nurses in providing sexual counseling. The purpose of this study was to determine the effectiveness of sexual counseling on family harmony of reproductive age chronic kidney disease patients undergoing hemodialysis. This research used quantitative research using pre-experimental one group pretest postest design with a total sample of 33 people. The results of this study showed an increase in family harmony scores before and after sexual counseling as much as 5.87 points with a p-value = 0.000 (p